Estudo das condições laborais em estações de tratamento de esgoto - Chagas Neto, Francisco das (2005)
Water pollution is growing drastically worldwide. Among the solutions adopted is the installation of wastewater treatment plants. They have to be considered industrial units at the service of the community that like any other unit of that type, suffers from problems related to hygiene and labor safety. In this research we studied labor hazards, ambient and operational, to which operators of treatment plants are exposed during the phases of industrial style waste water treatment. Methods applied include literature studies, questionnaires, verification of the existing safety norms, visiting of some treatment units of CAGECE – Companhia de Água e Esgoto do Ceará, and interviews with workers in order to learn about the working conditions and accidents occurred. The procedures applied and the safety and hygiene manuals were verified. We confirmed the lack of specific norms for the sanitation sector and of the “National Classification of Economic Activities – CNAE” that should consider waste water treatment, its workers and accidents they suffer. We found that many of the actual accidents were reported already decades ago; but manuals and procedures remained unchanged exhibiting, in addition, a language inaccessible for the workers. From the questionnaires, fully returned by the workers, we learned that the divulgement by CAGECE of safety procedures and accidents is transparent. This allowed a complete insight into accidents and risks occurring in waste water treatment plants.